Bacterial urocystitis in dogs and cats (classification, pathogenesis, causative agents, treatment, and prevention) - Yu. V. Martyniv (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Diseases of the urinary system are a common problem for small animals. Most often, pathological changes in the urinary bladder and urethra are registered in dogs and cats. In particular, urocystitis ranks first in the list of diseases of the lower urinary tract. The etiology of urocystitis can have a different genesis - infectious and non-infectious. Infectious urocystitis is divided into primary and secondary, which depends on the way of penetration of the uropathogen into the body. They have the same characteristics (bacterial pathogen, pathogenesis, clinical signs) as other infectious diseases, but no clear nosological classification exists. Most often, the causative agents of infectious urocystitis are bacteria that live on the body of animals as conditionally pathogenic microflora. These include escherichia, enterococci, corynebacteria, staphylococci, streptococci, proteus, and pseudomonads. Under favorable conditions, such as urolithiasis, immunosuppression, neoplasia, or congenital or acquired anatomical and functional defects of the urethra and bladder, these bacteria penetrate the urinary canal and begin to multiply uncontrollably there, which leads to the emergence of an infectious inflammatory process. Secondary bacterial urocystitis is more dangerous than primary ones, as constant relapses of the disease characterize their course. The final process of this disease is usually urosepsis. Therefore, according to various authors, the only effective therapy method for secondary infectious urocystitis is using antibiotics to which the pathogen is sensitive. This leads to antibiotic resistance of the bacterial microflora in the patient's body. The emergence of resistance of pathogens to antimicrobial agents makes further treatment of this pathology impossible. Preventive measures, proposed in various publications, ensure only the continuation of the remission of the disease. These measures cannot stop the recurrence of bacterial urocystitis and its irreversible consequences. Due to the cyclic nature of the pathogenetic process, dogs and cats suffering from secondary infectious urocystitis are classified as terminal patients. Alternative solutions to this problem have not yet been proposed. Analysis of literature data indicates that infectious urocystitis occurs more often as a complication of primary pathology. Still, after eliminating the initial cause, they play a vital role in the body of sick animals. Therefore, scientists' research should be directed to developing and implementing therapeutic measures and means that would neutralize bacterial agents without causing them to become resistant to antibiotics. The article describes the mechanisms of infection by uropathogens through the distal part of the urinary system and possible favorable factors that are the key to this process. The frequency of the disease occurrence in cats and dogs is given according to species, age, and sex. Issues of approach and treatment of bacterial urocystitis and related complications are highlighted. Based on the obtained data, an analysis was carried out, and a perspective vector was formed for further scientific research, which would eliminate the problem of this disease in small animals.